2014
DOI: 10.1002/2013jb010928
|View full text |Cite
|
Sign up to set email alerts
|

Understanding subsidence in the Mississippi Delta region due to sediment, ice, and ocean loading: Insights from geophysical modeling

Abstract: The processes responsible for land surface subsidence in the Mississippi Delta (MD) have been vigorously debated. Numerous studies have postulated a dominant role for isostatic subsidence associated with sediment loading. Previous computational modeling of present-day vertical land motion has been carried out in order to understand geodetic data. While the magnitudes of these measured rates have been reproduced, the model parameter values required have often been extreme and, in some cases, unrealistic. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 90 publications
4
87
1
Order By: Relevance
“…Depending on the estimate for sediment transport that is used, the magnitude of GISR loading effects is near the measurement limit: several tenths of millimeters per year uplift rate and several tenths of microgal per year gravity rate. The magnitude is comparable to a recent estimate of subsidence in the Mississippi delta (Yu et al, 2012;Wolstencroft et al, 2014) but somewhat smaller because of the larger sediment deposition area for the Fennoscandian ice sheet and the earlier demise of the ice sheet in the Barents Sea. The magnitude is smaller than a possible reference frame bias in GPS-derived uplift rates (Lidberg et al, 2010), and in the presence of other GIA model uncertainties, several tenths of millimeters a year do not appear to be significant.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Depending on the estimate for sediment transport that is used, the magnitude of GISR loading effects is near the measurement limit: several tenths of millimeters per year uplift rate and several tenths of microgal per year gravity rate. The magnitude is comparable to a recent estimate of subsidence in the Mississippi delta (Yu et al, 2012;Wolstencroft et al, 2014) but somewhat smaller because of the larger sediment deposition area for the Fennoscandian ice sheet and the earlier demise of the ice sheet in the Barents Sea. The magnitude is smaller than a possible reference frame bias in GPS-derived uplift rates (Lidberg et al, 2010), and in the presence of other GIA model uncertainties, several tenths of millimeters a year do not appear to be significant.…”
Section: Resultssupporting
confidence: 69%
“…Ivins et al (2007) force their surface loading model with an estimate of postglacial sedimentation rates of 10 mm yr −1 , compared to a background sedimentation rate over a glacial cycle of 1 mm yr −1 . Their modeling predicted present-day subsidence of 1-8 mm yr −1 although a more recent estimate reduces that amount to 0.5 mm yr −1 (Wolstencroft et al, 2014). Viscoelastic relaxation due to sediment deposition in the Indus River basin and Arabian Sea has been shown to cause changes in relative sea level of up to 2 m over 4000 years (Ferrier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dalca et al (2013) were the first to incorporate the gravitational, deformational, and rotational effects of sediment redistribution into a traditional GIA model (Figure 7a). The resulting theory has been used to 620 demonstrate that the impact of sediment erosion and deposition, associated with both fluvial and glacial systems, can alter relative sea-level by several metres over the course of a glacial cycle and rates of present-day deformation by a few tenths of a mm/yr (Wolstencroft et al, 2014;Ferrier et al, 2015;Kuchar et al, 2017;van der Wal and IJpelaar, 2017 magnitude of the perturbation due to sediment loading is small, it is greater than the precision of modern geodetic methods, and hence has the potential to bias contemporary estimates of sea-level change (Ferrier et al, 2015;van der Wal and IJpelaar, 625 2017). Perhaps the most important finding of these preliminary studies is the observation that in order for relative sea-level indicators to be used to constrain past global ice volumes, they must first be corrected for the effects of both glacial and sedimentary isostasy (Ferrier et al, 2015).…”
Section: Sedimentary Isostasy 615mentioning
confidence: 99%
“…Wolstencroft et al (2014) and Kuchar et al (2017) both found that including the effects of sedimentary isostasy did not bring agreement between model predictions and GPS-derived observations of contemporary land motion around the Mississippi Delta, and they concluded that sediment compaction must play a significant role (Figure 7b). To address this Ferrier et al (2017) have updated the theory developed 635…”
Section: Sedimentary Isostasy 615mentioning
confidence: 99%
“…SLIPs in the vicinity of the Mississippi Delta were corrected for the influence of sediment loading [Wolstencroft et al, 2014] as this effect is not included in the model applied here. Details of this correction are also provided in Section 3 of Appendix S1.…”
Section: Datamentioning
confidence: 99%